Clothesline Smart Device Design Based on Iot Device - Mulawarman Daulay; Solly Aryza Lubis; Zuraidah Tharo (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Drying clothes is a process of daily activities. Drying clothes through the drying process is a traditional method that is still widely used in various regions. However, the process of drying traditional clothes is often a challenge for people or individuals who have limited space and time, especially if the drying is done at home while at the same time not at home. So it takes innovation of smart clothesline devices based on the Internet of Things (IoT) that can help optimize the drying process of clothes. In designing and manufacturing this automatic clothes drying system uses two sensors, namely water sensors and light sensors. Both of these sensors function as weather detectors. If it rains, the water sensor will respond by sending voltage to the circuit and then moving the servo motor to rotate to the right or left so as to make the clothesline enter a closed room. When the clothesline enters, Arduino will give a command to the GSM module SIM800L to give a notification in the form of an sms that the clothesline has been inserted. Similarly, with the light sensor, when the rain has stopped, the light sensor responds to sunlight so that it makes the servo motor move to remove the clothesline.